Evidence for a metamagnetic transition in the heavy Fermion system CeTiGe - Deppe, M. (2010)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina